Titanium adsorbing material for extracting lithium from salt lake and preparation method of titanium adsorbing material

The structure of titanium-based adsorption materials is optimized through three-stage magnetic field sintering, and the problem of insufficient adsorption capacity and desorption rate of titanium-based adsorption materials is solved, and efficient and stable titanium-based adsorption materials are provided to meet the needs of industrial production of lithium extraction in salt lakes.

CN119281285AActive Publication Date: 2025-01-10SICHUAN TAILI XINGKUN NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411408716.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-10
Estimated Expiration
2044-10-10

AI Technical Summary

Technical Problem

The existing titanium-based adsorption materials have limited adsorption capacity and low desorption rate during the preparation process, making it difficult to meet the needs of industrial production of lithium extraction in salt lakes.

Method used

The three-stage magnetic field sintering method is adopted to control the conditional parameters of each stage, including the mixing of titanium source and lithium source, the magnetic field sintering temperature and time, optimize the structure and surface properties of the material, and improve the adsorption capacity and desorption rate of lithium elements.

Benefits of technology

It significantly improves the lithium element adsorption capacity and desorption rate of titanium-based adsorbent materials, and provides an efficient and stable titanium-based adsorbent material to meet the needs of the field of lithium extraction in salt lakes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119281285A_ABST
    Figure CN119281285A_ABST
Patent Text Reader

Abstract

The invention relates to a salt lake lithium extraction titanium adsorption material and a preparation method thereof, and relates to the technical field of adsorption materials.The preparation method of the salt lake lithium extraction titanium adsorption material comprises the following steps that a titanium source and a lithium source are mixed and then subjected to first magnetic field sintering, and a first precursor is obtained; performing second magnetic field sintering on the first precursor to obtain a second precursor; performing third magnetic field sintering on the second precursor to obtain a third precursor; adding the third precursor into an acid solution for acidification, and then filtering and drying to obtain the titanium adsorption material for extracting lithium from the salt lake. According to the method, a three-section magnetic field sintering mode is adopted, the lithium element adsorption capacity and desorption rate of the obtained titanium system adsorption material are remarkably improved by controlling condition parameters of all stages, the efficient and stable titanium system adsorption material is provided for the field of salt lake lithium extraction, and the defects in the prior art are overcome.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adsorption materials, and in particular to a titanium-based adsorption material for lithium extraction from salt lakes and a preparation method thereof. Background Art

[0002] As the global demand for renewable energy grows, the application of lithium as a key material in battery technology and energy storage systems is becoming increasingly important. However, traditional lithium extraction methods, such as magnesium metal method or chemical method, face many challenges in terms of environment, cost and resource utilization. In particular, the technical difficulty and economic cost of extracting lithium from salt lake brine are even more significant. Therefore, it is particularly important to develop efficient, environmentally friendly and sustainable lithium extraction technology.

[0003] Among the existing salt lake lithium extraction technologies, solvent extraction, precipitation crystallization, membrane separation, etc. each have their own advantages and disadvantages, but all have limitations to varying degrees. Although the solvent extraction method has certain applications in high magnesium-lithium ratio salt lake systems, it is prone to the hidden dangers of three-phase, corrosion of process equipment, and solution leakage that pollutes the environment, which limits its promotion and application. Although membrane separation technology is efficient and environmentally friendly, its high energy consumption and poor membrane durability also hinder its industrialization process. In contrast, the adsorption method has developed rapidly in the field of lithium extraction from salt lakes in recent years due to its advantages such as low cost, simple operation, green environmental protection, high selectivity and wide range of applications. The core of the adsorption method is to select or design and synthesize adsorption materials with efficient recognition capabilities for lithium ions, and to achieve selective separation and recovery of lithium ions through specific physical or chemical reactions.

[0004] Among adsorption materials, titanium-based adsorbents have attracted much attention due to their unique properties. As an emerging lithium ion adsorbent, titanium-based materials have good cycle stability and high specific surface area, and can effectively adsorb and release lithium ions. In addition, titanium-based adsorbents also have the characteristics of controllable preparation, and their morphology and structure can be adjusted according to different application requirements. These advantages make titanium-based adsorbents show great application potential in the field of lithium extraction from salt lakes. However, existing titanium-based adsorbent materials often have problems such as limited adsorption capacity and low desorption rate during the preparation process, which makes it difficult to meet the needs of industrial production of lithium extraction from salt lakes. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a titanium-based adsorption material for lithium extraction from salt lakes and a preparation method thereof.

[0006] In a first aspect, the present invention provides a method for preparing a titanium-based adsorbent material for lithium extraction from a salt lake, the method comprising the following steps:

[0007] A titanium source and a lithium source are mixed, and then subjected to a first magnetic field sintering to obtain a first precursor;

[0008] Sintering the first precursor in a second magnetic field to obtain a second precursor;

[0009] sintering the second precursor in a third magnetic field to obtain a third precursor;

[0010] Adding the third precursor into an acidic solution for acidification, filtering and drying, and obtaining the salt lake lithium-extracting titanium-based adsorption material;

[0011] The working condition parameters of the first magnetic field sintering include: the flux coil current is 2.5-5A, the temperature is 200-280°C, and the time is 1-2 hours;

[0012] The working condition parameters of the second magnetic field sintering include: the flux coil current is 12-15A, the temperature is 670-750°C, and the time is 4-6 hours;

[0013] The working condition parameters of the third magnetic field sintering include: the flux coil current is 6-10A, the temperature is 300-400°C, and the time is 1-2 hours.

[0014] Furthermore, the working condition parameters of the first magnetic field sintering include: the flux coil current is 4A, the temperature is 260°C, and the time is 1 to 2 hours.

[0015] Furthermore, the working condition parameters of the second magnetic field sintering include: the flux coil current is 13A, the temperature is 720°C, and the time is 4 to 6 hours.

[0016] Furthermore, the working condition parameters of the third magnetic field sintering include: the flux coil current is 8A, the temperature is 380°C, and the time is 1 to 2 hours.

[0017] Furthermore, the molar ratio of Ti in the titanium source to Li in the lithium source is 1:(2-2.2).

[0018] Furthermore, the titanium source includes at least one of titanium dioxide, metatitanic acid, titanium chloride, titanium sulfate and tetrabutyl titanate.

[0019] Furthermore, the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium chloride, lithium acetate and lithium nitrate.

[0020] Furthermore, the working condition parameters of the acidification include: the acidification temperature is 45 to 55° C., and the acidification time is 10 to 20 hours.

[0021] Furthermore, the acidic solution is a hydrochloric acid solution with a molar concentration of 0.01-0.1 mol / L.

[0022] In a second aspect, the present invention provides a titanium-based adsorption material for lithium extraction from salt lakes, wherein the titanium-based adsorption material for lithium extraction from salt lakes is prepared by the preparation method described in any one of the first aspects.

[0023] The above technical solution provided by the embodiment of the present invention has at least the following advantages compared with the prior art:

[0024] The embodiment of the present invention provides a titanium-based adsorption material for lithium extraction from salt lakes and a preparation method thereof. The present invention adopts a three-stage magnetic field sintering method and significantly improves the lithium adsorption capacity and desorption rate of the obtained titanium-based adsorption material by controlling the condition parameters of each stage, providing an efficient and stable titanium-based adsorption material for the field of lithium extraction from salt lakes, making up for the shortcomings of the prior art. Specifically:

[0025] The first stage: select suitable titanium source (such as titanium dioxide, titanate, etc.) and lithium source (such as lithium carbonate, lithium hydroxide, etc.) for mixing, and perform preliminary sintering under the first magnetic field sintering conditions. This step is to promote the initial chemical reaction between the titanium source and the lithium source. The introduction of the magnetic field can promote the formation of a more ordered structure and initially form a precursor structure, avoiding the premature formation of a dense structure that hinders subsequent reactions, and laying the foundation for subsequent steps.

[0026] The second stage: Based on the first precursor, the magnetic field strength and sintering temperature are adjusted to carry out the second magnetic field sintering. The main purpose of this stage is to further optimize the crystal structure of the material, enhance the stability and specific surface area of ​​the material, and the continuous action of the magnetic field helps to refine the grains, increase the porosity and active sites of the material, and is conducive to improving the lithium adsorption capacity of the titanium-based adsorption material.

[0027] The third stage: After the first two sinterings, the third magnetic field sintering stage further consolidates and optimizes the structural properties of the material. At the same time, by adjusting the sintering conditions (such as lowering the temperature and changing the magnetic field strength), the surface properties of the material are fine-tuned to make it more conducive to the adsorption and desorption of lithium ions and improve the stability of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0030] Figure 1A schematic flow chart of a method for preparing a titanium-based adsorption material for lithium extraction from a salt lake provided in an embodiment of the present invention.

[0031] Figure 2 This is an electron microscope characterization image of the titanium-based adsorption material for lithium extraction from salt lakes provided in Example 1 of the present invention.

[0032] Figure 3 This is an electron microscope characterization image of the titanium-based adsorption material for lithium extraction from salt lakes provided in Comparative Example 1 of the present invention.

[0033] Figure 4 This is an electron microscope characterization image of the titanium-based adsorption material for lithium extraction from salt lakes provided in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0036] In the first aspect, the present invention provides a method for preparing a lithium-titanium adsorption material from a salt lake, such as Figure 1 As shown, the method for preparing the lithium-titanium adsorption material from salt lake comprises the following steps:

[0037] A titanium source and a lithium source are mixed, and then subjected to a first magnetic field sintering to obtain a first precursor;

[0038] Sintering the first precursor in a second magnetic field to obtain a second precursor;

[0039] sintering the second precursor in a third magnetic field to obtain a third precursor;

[0040] Adding the third precursor into an acidic solution for acidification, filtering and drying, and obtaining the salt lake lithium-extracting titanium-based adsorption material;

[0041] The working condition parameters of the first magnetic field sintering include: the flux coil current is 2.5-5A, the temperature is 200-280°C, and the time is 1-2 hours;

[0042] The working condition parameters of the second magnetic field sintering include: the flux coil current is 12-15A, the temperature is 670-750°C, and the time is 4-6 hours;

[0043] The working condition parameters of the third magnetic field sintering include: the flux coil current is 6-10A, the temperature is 300-400°C, and the time is 1-2 hours.

[0044] The embodiment of the present invention provides a method for preparing a titanium-based adsorption material for lithium extraction from salt lakes. The present invention adopts a three-stage magnetic field sintering method, and by controlling the condition parameters of each stage, the lithium adsorption capacity and desorption rate of the obtained titanium-based adsorption material are significantly improved, providing an efficient and stable titanium-based adsorption material for the field of lithium extraction from salt lakes, making up for the shortcomings of the prior art. Specifically:

[0045] The first stage: select suitable titanium source (such as titanium dioxide, titanate, etc.) and lithium source (such as lithium carbonate, lithium hydroxide, etc.) for mixing, and perform preliminary sintering under the first magnetic field sintering conditions. This step is to promote the initial chemical reaction between the titanium source and the lithium source. The introduction of the magnetic field can promote the formation of a more ordered structure and initially form a precursor structure, avoiding the premature formation of a dense structure that hinders subsequent reactions, and laying the foundation for subsequent steps.

[0046] The second stage: Based on the first precursor, the magnetic field strength and sintering temperature are adjusted to carry out the second magnetic field sintering. The main purpose of this stage is to further optimize the crystal structure of the material, enhance the stability and specific surface area of ​​the material, and the continuous action of the magnetic field helps to refine the grains, increase the porosity and active sites of the material, and is conducive to improving the lithium adsorption capacity of the titanium-based adsorption material.

[0047] The third stage: After the first two sinterings, the third magnetic field sintering stage further consolidates and optimizes the structural properties of the material. At the same time, by adjusting the sintering conditions (such as lowering the temperature and changing the magnetic field strength), the surface properties of the material are fine-tuned to make it more conducive to the adsorption and desorption of lithium ions and improve the stability of the material.

[0048] In some specific embodiments, the working condition parameters of the first magnetic field sintering include: the flux coil current is 4A, the temperature is 260°C, and the time is 1 to 2 hours.

[0049] In some specific embodiments, the working condition parameters of the second magnetic field sintering include: the flux coil current is 13A, the temperature is 720°C, and the time is 4 to 6 hours.

[0050] In some specific embodiments, the working condition parameters of the third magnetic field sintering include: the flux coil current is 8A, the temperature is 380°C, and the time is 1 to 2 hours.

[0051] In some specific embodiments, the molar ratio of Ti in the titanium source to Li in the lithium source is 1:(2-2.2), preferably 1:2.1.

[0052] In some specific embodiments, the titanium source includes at least one of titanium dioxide, metatitanic acid, titanium chloride, titanium sulfate, and tetrabutyl titanate.

[0053] In some specific embodiments, the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium chloride, lithium acetate and lithium nitrate.

[0054] In some specific embodiments, the working condition parameters of the acidification include: the acidification temperature is 45 to 55° C., and the acidification time is 10 to 20 hours.

[0055] In some specific embodiments, the acidic solution is a hydrochloric acid solution with a molar concentration of 0.01-0.1 mol / L, and a hydrochloric acid solution of 0.01 mol / L is optional.

[0056] In the second aspect, based on the same inventive concept, the present invention provides a titanium-based adsorption material for lithium extraction from salt lakes, wherein the titanium-based adsorption material for lithium extraction from salt lakes is prepared by the preparation method described in any one of the first aspects.

[0057] The titanium-based adsorbent material for extracting lithium from salt lakes provided by the present invention is realized based on the preparation method described in any one of the first aspects. Therefore, the titanium-based adsorbent material for extracting lithium from salt lakes has at least the beneficial effects of the technical solutions described in any one of the first aspects, which will not be described one by one here.

[0058] It should be noted that the component raw materials involved in the titanium-based adsorption material for lithium extraction from salt lakes and the preparation method thereof provided in the embodiments of the present invention, unless otherwise specified or specified, can be directly commercially available products or homemade using existing public preparation methods; at the same time, the steps and parameters involved, unless otherwise specified or specified, can be carried out according to the existing processing technology of titanium-based adsorption materials or directly using existing equipment, and the present invention document will not describe them one by one.

[0059] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are intended only to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.

[0060] Example 1

[0061] This example provides a salt lake lithium extraction titanium adsorption material, and the preparation method of the salt lake lithium extraction titanium adsorption material comprises the following steps:

[0062] Step (1): mixing a titanium source (specifically metatitanic acid) and a lithium source (specifically lithium carbonate) and adding the mixture into a magnetic field sintering furnace, heating the mixture from room temperature to 260° C. at a rate of 10° C. / min with a magnetic flux coil current of 4A for 1.5 hours, and cooling the mixture in the furnace to obtain a first precursor; wherein the molar ratio of Ti in the titanium source to Li in the lithium source is 1:2.1;

[0063] Step (2): sintering the first precursor obtained in step (1) in a second magnetic field for 5 hours at a flux coil current of 13A and a temperature increase rate of 10°C / min from room temperature to 720°C, followed by furnace cooling to obtain a second precursor;

[0064] Step (3): sintering the second precursor obtained in step (2) in a third magnetic field for 1.5 hours at a flux coil current of 8A and a temperature increase rate of 10°C / min from room temperature to 380°C, followed by furnace cooling to obtain a third precursor;

[0065] Step (4): immerse the third precursor obtained in step (3) in a 0.01 mol / L hydrochloric acid solution for acidification at a temperature of 50°C for 18 hours, filter and vacuum dry the obtained solid at 50°C to constant weight to obtain the salt lake lithium-extracted titanium adsorption material.

[0066] Example 2

[0067] This example provides a salt lake lithium extraction titanium adsorption material, and the preparation method of the salt lake lithium extraction titanium adsorption material comprises the following steps:

[0068] Step (1): mixing a titanium source (specifically metatitanic acid) and a lithium source (specifically lithium carbonate) and adding the mixture to a magnetic field sintering furnace, heating the mixture from room temperature to 280° C. at a rate of 10° C. / min with a magnetic flux coil current of 2.5 A for 1.5 hours, and cooling the mixture in the furnace to obtain a first precursor; wherein the molar ratio of Ti in the titanium source to Li in the lithium source is 1:2.1;

[0069] Step (2): subjecting the first precursor obtained in step (1) to a second magnetic field sintering for 6 hours at a flux coil current of 15 A and a temperature increase rate of 10° C. / min from room temperature to 670° C., followed by furnace cooling to obtain a second precursor;

[0070] Step (3): sintering the second precursor obtained in step (2) in a third magnetic field for 1.5 hours at a flux coil current of 6A and a temperature increase rate of 10°C / min from room temperature to 300°C, followed by furnace cooling to obtain a third precursor;

[0071] Step (4): immerse the third precursor obtained in step (3) in a 0.01 mol / L hydrochloric acid solution for acidification at a temperature of 50°C for 18 hours, filter and vacuum dry the obtained solid at 50°C to constant weight to obtain the salt lake lithium-extracted titanium adsorption material.

[0072] Example 3

[0073] This example provides a salt lake lithium extraction titanium adsorption material, and the preparation method of the salt lake lithium extraction titanium adsorption material comprises the following steps:

[0074] Step (1): mixing a titanium source (specifically metatitanic acid) and a lithium source (specifically lithium carbonate) and adding the mixture into a magnetic field sintering furnace, performing a first magnetic field sintering for 1.5 hours at a rate of 10°C / min from room temperature to 200°C with a flux coil current of 5A, and cooling the mixture in the furnace to obtain a first precursor; wherein the molar ratio of Ti in the titanium source to Li in the lithium source is 1:2.1;

[0075] Step (2): subjecting the first precursor obtained in step (1) to a second magnetic field sintering for 4 hours at a flux coil current of 12A and a temperature increase rate of 10°C / min from room temperature to 750°C, followed by furnace cooling to obtain a second precursor;

[0076] Step (3): sintering the second precursor obtained in step (2) in a third magnetic field for 1.5 hours at a flux coil current of 10 A and a temperature increase rate of 10° C. / min from room temperature to 400° C., followed by furnace cooling to obtain a third precursor;

[0077] Step (4): immerse the third precursor obtained in step (3) in a 0.01 mol / L hydrochloric acid solution for acidification at a temperature of 50°C for 18 hours, filter and vacuum dry the obtained solid at 50°C to constant weight to obtain the salt lake lithium-extracted titanium adsorption material.

[0078] Comparative Example 1

[0079] This example provides a titanium-based adsorption material for lithium extraction from salt lakes and a preparation method thereof. The only difference from Example 1 is that the flux coil currents of the first magnetic field sintering and the second magnetic field sintering are both 13A and the temperatures are both 720°C; the remaining steps and parameters are the same.

[0080] The preparation method of the above-mentioned salt lake lithium-extraction titanium adsorption material comprises the following steps:

[0081] Step (1): mixing a titanium source (specifically metatitanic acid) and a lithium source (specifically lithium carbonate) and adding the mixture into a magnetic field sintering furnace, performing a first magnetic field sintering for 1.5 hours at a rate of 10°C / min at a magnetic flux coil current of 13A from room temperature to 720°C, and cooling the mixture in the furnace to obtain a first precursor; wherein the molar ratio of Ti in the titanium source to Li in the lithium source is 1:2.1;

[0082] Step (2): sintering the first precursor obtained in step (1) in a second magnetic field for 5 hours at a flux coil current of 13A and a temperature increase rate of 10°C / min from room temperature to 720°C, followed by furnace cooling to obtain a second precursor;

[0083] Step (3): sintering the second precursor obtained in step (2) in a third magnetic field for 1.5 hours at a flux coil current of 13A and a temperature increase rate of 10°C / min from room temperature to 720°C, followed by furnace cooling to obtain a third precursor;

[0084] Step (4): immerse the third precursor obtained in step (3) in a 0.01 mol / L hydrochloric acid solution for acidification at a temperature of 50°C for 18 hours, filter and vacuum dry the obtained solid at 50°C to constant weight to obtain the salt lake lithium-extracted titanium adsorption material.

[0085] Comparative Example 2

[0086] This example provides a titanium-based adsorption material for lithium extraction from salt lakes and a preparation method thereof, which differs from Example 1 only in that sintering is not performed in a magnetic field atmosphere; the remaining steps and parameters are the same.

[0087] The preparation method of the above-mentioned salt lake lithium-extraction titanium adsorption material comprises the following steps:

[0088] Step (1): mixing a titanium source (specifically metatitanic acid) and a lithium source (specifically lithium carbonate) and adding the mixture into a sintering furnace, heating the mixture from room temperature to 260° C. at a rate of 10° C. / min for 1.5 hours, and cooling the mixture in the furnace to obtain a first precursor; wherein the molar ratio of Ti in the titanium source to Li in the lithium source is 1:2.1;

[0089] Step (2): subjecting the first precursor obtained in step (1) to a second sintering process under the condition of heating from room temperature to 720° C. at a rate of 10° C. / min for 5 hours, and cooling in the furnace to obtain a second precursor;

[0090] Step (3): the second precursor obtained in step (2) is subjected to a third sintering at a temperature rising from room temperature to 380° C. at a rate of 10° C. / min for 1.5 hours, and then cooled in the furnace to obtain a third precursor;

[0091] Step (4): immerse the third precursor obtained in step (3) in a 0.01 mol / L hydrochloric acid solution for acidification at a temperature of 50°C for 18 hours, filter and vacuum dry the obtained solid at 50°C to constant weight to obtain the salt lake lithium-extracted titanium adsorption material.

[0092] Test Case

[0093] In this example, the performance of the titanium-based adsorption materials for lithium extraction from salt lakes obtained in the above-mentioned Examples 1 to 3 and Comparative Examples 1 to 2 was tested according to the existing testing methods.

[0094] Test method: 1) Prepare high-concentration brine to simulate the salt lake water environment, its composition mainly includes: Na + , Li concentration of 320ppm + , K concentration of 2450ppm + , Mg concentration of 940ppm 2+ ; 2) Weigh 1 g of the titanium-based adsorbent material for lithium extraction from salt lakes obtained in the above-mentioned Examples 1 to 3 and Comparative Examples 1 to 2, respectively, and put it into 200 mL of brine for stirring for 3 hours, then filter them to obtain the adsorption filtrate, measure the ion content using an inductively coupled plasma spectrometer, and calculate the adsorption capacity of the titanium-based adsorbent material for lithium extraction from Li salt lakes provided in each embodiment and comparative example according to Formula 1; 3) Wash each portion of the filtered solid phase (i.e., adsorbent) with 1 L of pure water and dry it at 60°C, weigh 0.5 g of the solid phase and put it into 100 mL of The mixture was subjected to desorption at 40°C for 1 h in a hydrochloric acid solution with a pH value of 1. After the reaction, the desorption filtrate was obtained by filtration. The ion content was measured by an inductively coupled plasma spectrometer. The desorption capacity of the titanium-based adsorption material for lithium extraction from Li salt lake provided in each embodiment and the comparative example was calculated according to Formula 2. The Li desorption rate of the titanium-based adsorption material for lithium extraction from Li salt lake provided in each embodiment and the comparative example was calculated according to Formula 3. Wherein, Formula 1: Li adsorption capacity (mg / g) = (Li concentration before adsorption test - Li concentration after adsorption test) × 0.2 ÷ 1; Formula 2: Li desorption capacity (mg / g) = (Li concentration in desorption liquid × 0.1) ÷ 0.5; Formula 3: Li desorption rate (%) = (Li desorption capacity ÷ Li adsorption capacity) × 100%.

[0095] The test results are shown in Table 1.

[0096] Table 1

[0097] Test samples Li adsorption capacity (mg / g) Li desorption capacity (mg / g) Li desorption rate (%) Example 1 32.1 31.7 98.8 Example 2 24.9 22.5 90.4 Example 3 25.2 23.2 92.1 Comparative Example 1 19.5 11.4 58.5 Comparative Example 2 17.8 7.7 43.3

[0098] As can be seen from Table 1, compared with Comparative Examples 1-2, the titanium-based adsorbent material for lithium extraction from salt lakes provided in the embodiment of the present invention has a higher Li adsorption capacity and Li desorption rate, which can meet the needs of industrial production of lithium extraction from salt lakes, and the effect of Example 1 is the best. In addition, the electron microscopy characterization of the titanium-based adsorbent material for lithium extraction from salt lakes obtained in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention is shown as follows: Figure 2 , Figure 3 and Figure 4 As shown, by comparison, it can be seen that the titanium-based adsorption material for lithium extraction from salt lakes obtained in the embodiment of the present invention not only has a smaller particle size of 30-50 nm, but also has an ordered structure and a better morphology.

[0099] In summary, the embodiments of the present invention provide a titanium-based adsorption material for lithium extraction from salt lakes and a preparation method thereof. The present invention adopts a three-stage magnetic field sintering method and significantly improves the lithium adsorption capacity and desorption rate of the obtained titanium-based adsorption material by controlling the condition parameters of each stage, thereby providing an efficient and stable titanium-based adsorption material for the field of lithium extraction from salt lakes, making up for the shortcomings of the prior art.

[0100] Various embodiments of the present invention may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0101] The foregoing is merely a specific embodiment of the present invention, which enables those skilled in the art to understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features claimed herein.

Claims

1. A method for preparing a lithium-titanium adsorption material from a salt lake, characterized in that: The method for preparing the titanium-based adsorption material for lithium extraction from salt lakes comprises the following steps: A titanium source and a lithium source are mixed, and then subjected to a first magnetic field sintering to obtain a first precursor; Sintering the first precursor in a second magnetic field to obtain a second precursor; sintering the second precursor in a third magnetic field to obtain a third precursor; Adding the third precursor into an acidic solution for acidification, filtering and drying, and obtaining the salt lake lithium-extracting titanium-based adsorption material; The working condition parameters of the first magnetic field sintering include: the flux coil current is 2.5-5A, the temperature is 200-280°C, and the time is 1-2 hours; The working condition parameters of the second magnetic field sintering include: the flux coil current is 12-15A, the temperature is 670-750°C, and the time is 4-6 hours; The working condition parameters of the third magnetic field sintering include: the flux coil current is 6-10A, the temperature is 300-400°C, and the time is 1-2 hours.

2. The method for preparing a titanium-based adsorbent material for lithium extraction from salt lakes according to claim 1, characterized in that: The working condition parameters of the first magnetic field sintering include: the flux coil current is 4A, the temperature is 260°C, and the time is 1 to 2 hours.

3. The method for preparing a titanium-based adsorbent material for lithium extraction from salt lakes according to claim 1, characterized in that: The working condition parameters of the second magnetic field sintering include: the flux coil current is 13A, the temperature is 720°C, and the time is 4 to 6 hours.

4. The method for preparing a titanium-based adsorbent material for lithium extraction from salt lakes according to claim 1, characterized in that: The working condition parameters of the third magnetic field sintering include: the flux coil current is 8A, the temperature is 380°C, and the time is 1 to 2 hours.

5. The method for preparing a titanium-based adsorbent material for lithium extraction from salt lakes according to claim 1, characterized in that: The molar ratio of Ti in the titanium source to Li in the lithium source is 1:(2-2.2).

6. The method for preparing a titanium-based adsorbent material for lithium extraction from salt lakes according to claim 1, characterized in that: The titanium source includes at least one of titanium dioxide, metatitanic acid, titanium chloride, titanium sulfate and tetrabutyl titanate.

7. The method for preparing a titanium-based adsorbent material for lithium extraction from salt lakes according to claim 1, characterized in that: The lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium chloride, lithium acetate and lithium nitrate.

8. The method for preparing a titanium-based adsorbent material for lithium extraction from salt lakes according to claim 1, characterized in that: The working condition parameters of the acidification include: the acidification temperature is 45 to 55° C., and the acidification time is 10 to 20 hours.

9. The method for preparing a titanium-based adsorbent material for lithium extraction from salt lakes according to claim 1, characterized in that: The acidic solution is a hydrochloric acid solution with a molar concentration of 0.01-0.1 mol / L.

10. A titanium-based adsorption material for lithium extraction from salt lakes, characterized in that: The titanium-based adsorption material for lithium extraction from salt lakes is prepared by the preparation method described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Magnetic biochar quantum dot composite adsorbent as well as preparation method and using method thereof

    CN103920461A

  • Sintering method of high-titanium vanadium-titanium magnetite concentrates

    CN106244800A

  • Preparation method of titanium adsorbing material for extracting lithium from salt lake, product obtained by preparation method and application of product

    CN115945162A

  • Lithium iron phosphate composite material with high compaction and long cycle performance and preparation method thereof

    CN117012889A

  • Positive electrode material for high voltage lithium battery, battery, preparation method therefor and use thereof

    WO2018090956A1

Cited By

  • High-temperature-resistant, high-adsorption and solution-loss-resistant titanium salt lake lithium extraction adsorbent and application thereof

    CN121003970A

  • High-temperature-resistant lithium-extraction adsorbent with high adsorption and anti-dissolution loss and use thereof

    CN121003970B